Analisis Kebutuhan Program Promosi Pencegahan Diare pada Anak Berusia di Bawah Dua Tahun - Elfi Rahmawati, Retna Siwi Padmawati, Rendra Widyatama (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Diarrhea  is one  of environmental  based  diseases  and  still  the  cause  of major  health problems  in Indonesia.  It  is attributed  to  the poor condition of basic sanitation, physical environment and  the poor behavior of community  in personal hygiene. Diarrhea  is considered as one of  the  infectious diseases and  the main cause of mortality  and morbidity  in children  under-five particularly  under  two-years  old. Various  health promotion  activities have been conducted  to control diarrhea disease, yet  the  diarrhea  incident  rate still high. Even  for certain period there has  been  an  increasing number  of  diarrhea  patients.Objective: This  research was  aimed  at  describing  the community’s  need  for  the  health  education  of  diarrhea prevention.Method:  This was  a  qualitative  research using  case  study  approach. Data  collection was  conducted  by  in depth  interview,  focus  group  discussion, observation  and  document  study. Research  informants were mothers who have  children below  two  years  old and  health education  stakeholders. Data was  analyzed  using    interactive analysis.Result:   The promotion  program  for  diarrhea prevention  that  has  been conducted  in Primary Health Care  of Piyungan was not  able  to  diminish  various  inappropriate  perceptions  and  assumptions  toward diarrhea.  The community  could not  see  the  relation  between  diarrhea with  environment and  breastfeeding. Community’s  need toward  diarrhea  information was all materials  related with diarrhea. The  method  to  convey was  through  speech that used  leaflet,  folder  and booklet. The  information  source  that  suitable  to  give  information was  health  care provider  in  regulars meeting  every month.Conclusion:  the suitable  health promotion  for diarrhea  is speech  by health  provider using  leaflet, booklet  and folder.  Education material  should  be  focused  on  diarrhea prevention,  especially  on  the  relationship  between environment  and breastfeeding  and  diarrhea  incidents.Keywords: need  assessment,  promotion  program,  diarrhea  prevention